Gentrifiers and attitudes towards agency: A new typology. Evidence from Tel Aviv-Jaffa, Israel. (May 2020) - Kaddar, Merav
This article offers a new typology (and therefore understanding) of gentrifiers, dividing them into four ideal types: Shruggers, Agonisers, Upgraders and Activists. Based on 32 in-depth interviews and focusing on the political aspect of gentrifiers' behaviour, namely their agency, the article suggests that gentrifiers' attitudes towards agency are affected by two main factors: their sense of efficacy, and their interest in remedying the allegedly negative political and urban outcomes of gentrification. These two factors yield the above-mentioned four ideal types of agency among gentrifiers. In addition, I find that the duration of their residence in the neighbourhood moderates gentrifiers' attitudes and perceptions, thus affecting their behaviour.